Comparative study on water structures of poly(tetrahydrofurfuryl acrylate) and poly(2-hydroxyethyl methacrylate) by nuclear magnetic resonance spectroscopy. Issue 13 (2nd September 2021) - Mochizuki, Akira; Oda, Yoshiki; Miwa, Yuko
Abstract: It is well known that poly(2-methoxyethyl acrylate) (PMEA) has good blood compatibility and its performance is attributed to its water structure. Recently, we applied solution nuclear magnetic resonance spectroscopy (solution-NMR) for analyzing the water structure in PMEA at ambient temperature and concluded that this method is useful because of the clear observation of the resonance peaks at low and high magnetic field (downfield and upfield, respectively) areas indicating the existence of more than two types of water. The present study was performed to compare the water structure of poly(tetrahydrofurfuryl acrylate) (PTHFA) and poly(2-hydroxyethyl methacrylate) (PHEMA) using solution 2 H-NMR and deuterium oxide as water at the temperature range 15–45 °C. It was found that PTHFA has a different water structure from that of PHEMA. Water in PTHFA clearly showed two resonance peaks at downfield and upfield areas, with different spin-lattice relaxation times, T1 2H (high and low values, respectively). These observations are similar to those of PMEA. In contrast, PHEMA showed only one broad resonance peak (at downfield) with a low T1 2H value. Based on these observations, this study discusses the effect of water structures on the blood compatibility of these polymers.